2020
DOI: 10.1371/journal.pone.0237880
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin for treatment of ventilator-associated pneumonia in a setting of high carbapenem resistance

Abstract: Objectives To analyse the use of polymyxins for the treatment of ventilator-associated pneumonia (VAP) at a teaching hospital where carbapenem-resistant gram-negative bacteria are endemic. Patients and methods This was a historical cohort study of patients receiving polymyxins to treat VAP in ICUs at a public university hospital in southern Brazil between January 1, 2017 and January 31, 2018. Results During the study period, 179 cases of VAP were treated with polymyxins. Of the 179 patients, 158 (88.3%) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition, 10 other studies were excluded, mainly because of inappropriate study type (n=5), descriptive studies (n=4) or for not having identified A. baumannii (n=1). Finally, 5 articles [ 11 - 15 ] were included in the final review: four from PubMed [ 12 - 15 ] and one from BVS [ 11 ]. A manual search was performed in the references of the included articles and resulted in no further studies to be included.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, 10 other studies were excluded, mainly because of inappropriate study type (n=5), descriptive studies (n=4) or for not having identified A. baumannii (n=1). Finally, 5 articles [ 11 - 15 ] were included in the final review: four from PubMed [ 12 - 15 ] and one from BVS [ 11 ]. A manual search was performed in the references of the included articles and resulted in no further studies to be included.…”
Section: Resultsmentioning
confidence: 99%
“…Risk factors of A. baumannii infection were assessed in 3 studies [ 12 ,14,15]. Moreover, the use of invasive devices, previous antibiotic therapy, use of nasogastric tube, and hemodialysis increased the risks of infection [ 15 ]. Biofilm formation was described in 1 study, in which most isolates (76.8%) presented with this feature [ 12 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations